High gas barrier properties of novel urea-carbamate functionalized polydimethylsiloxane composites star-crosslinked by graphene oxide - Yuwei Gu; Lijun Chu; Quanxiao Dong; Peng Qiu; Stephen Jerrams; Shui Hu; Shipeng Wen (eXPRESS Polymer Letters)
Polydimethylsiloxane has the characteristics of low-temperature flexibility and excellent aging resistance. However, high molecule mobility and weak interactions between PDMS molecules result in poor mechanical strength and deficient gas barrier properties of PDMS composites. Herein, diamino-polydimethylsiloxane (PDMS) was reacted with 4,4′-diphenylmethane diisocyanate (MDI) and 1,4-butanediol (BDO) to form urea-carbamate functionalized PDMS (MDI-PDMS-BDO) with different hard segment contents. Furthermore, the modified graphene oxide (iGO) was obtained by the reaction between graphene oxide (GO) and MDI. iGO was further introduced into the functionalized PDMS to prepare iGO/urethane-urea functionalized PDMS composites (iGO/MDI-PDMS-BDO). An ordered structure was formed by the hard segments of the MDI-PDMS-BDO functionalized PDMS. A strong urea-based interface was also obtained between iGO and functionalized PDMS. iGO became the cross-linking center in the iGO/MDI-PDMS-BDO composites. Due to the ordered structure of hard segments and the iGO network formed in the PDMS composite with only 0.07 wt% iGO, the tensile strength and gas barrier properties of the iGO/MDI-PDMS-BDO composite were increased by 18 times and 64.27%, respectively, compared with pure PDMS.